Implementation of the Barangay Micro Business Enterprises (BMBE) Law: Impacts, Challenges, and Policy Recommendations - Jefferson R. Cruz; Rolando R. Calma; Luisito V. Correa, Jr.; Mario Alex S.J. Clarin; Ken Paul M. Espinosa (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study aimed to examine the implementation of the Barangay Micro Business Enterprises (BMBE) Law and its impacts and challenges as perceived by the business owners in the City of Malabon, Philippines, and proposed policy recommendations. The BMBE Law was enacted to promote the growth of microenterprises and stimulate local economic development in underserved communities. A descriptive-quantitative research design was employed to assess the law's impact on income generation, local competitiveness, and poverty alleviation of various business sectors. The results indicated that respondents generally perceived a very high level of BMBE Law implementation. Statistical analysis revealed a significant difference in local competitiveness when businesses were grouped by years in operation, whereas no significant differences were observed in income generation and poverty alleviation. Early-stage enterprises, operating for less than five years, reported a higher perceived economic contribution in terms of local competitiveness compared with longer-established firms. The findings of this study underscored the need for ongoing monitoring and support for microenterprises to optimize the benefits of the BMBE Law. The study highlighted the importance of tailored, sector-specific interventions that address the diverse experiences of microenterprises. Overall, the results provided valuable insights for policymakers and stakeholders seeking to strengthen the implementation and effectiveness of the BMBE Law, thereby advancing sustainable economic growth in the City of Malabon, Philippines.